Accounting and fiscal news 2010 - IONESCU, Cicilia (Annals of Spiru Haret University. Economic Series, 2010)
By decree of the Minister of Public Finance no. 3055/2009 for the adoption of the accounting Regulations in compliance with the European directives (that abolish completely the provisions of the 1752/2005 Decree), a series of modifications/news were introduced in the field of accounting, as well as in the fiscal field. These regulations are applicable starting the 1st of January 2010. The herewith material details the main accounting and fiscal news such as: news concerning the accounting procedures; news concerning the internal control, news concerning the companies’ stock-taking; anticipated disbursement system for the profit tax applicable starting 2010 by all the contributors; the regularization of the profit tax owed for 2009; clarifications regarding the certification of the annual profit tax declaration for 2009; the new regulations for the elaboration and deposition of the recapitulative declaration, as well as other declaration obligations associated to the beginning of the new year; important accounting aspects referring to the patrimony stock-taking at the end of 2009.